P068 Discovery of IBD3540: A Novel Gut-Restricted Glutamate Carboxypeptidase II Inhibitor with Preclinical Anti-Colitis Activity. (21st January 2022) - Peters, D; Norris, L; Tenora, L; Snajdr, I; Zhu, X; Sakamoto, S; Veeravalli, V; Thomas, A; Majer, P; Rais, R; Slusher, B
Abstract: Background: Glutamate carboxypeptidase II (GCPII) is robustly overexpressed in both Crohn's disease and ulcerative colitis and is a promising therapeutic target for IBD. We have previously published that systemically or enema administered small molecule GCPII inhibitors have efficacy in multiple mouse colitis models. While this is a highly encouraging activity profile for a candidate IBD drug, an oral dose route would be strongly preferred. Thus, here we develop and characterize a new class of GCPII inhibitors designed to be gut-restricted for oral administration, with the intention of selecting a lead inhibitor for further clinical development. Methods: Anti-inflammatory secondary bile acids lithocholic acid, deoxycholic acid and ursodeoxycholic acid were conjugated to GCPII inhibitor, 2-PMPA, yielding three novel constructs. These conjugates were screened for oral activity in murine dextran sulfate sodium (DSS) colitis, followed by detailed characterization of the most active inhibitor to: measure GCPII inhibition (IC50 ), confirm colon target engagement, evaluate plasma and colon pharmacokinetic profiles, compare efficacy versus standard-of-care agents, evaluate mechanisms of anti-inflammatory activity in vivo, confirm efficacy in a second colitis model (IL10 -/- ), and assess safety in standard preclinical assays. Results: The deoxycholic acid 2-PMPA conjugate, IBD3540, was identified as the lead inhibitor (IC50 = 4nM). Oral IBD3540 was robustly efficacious in acute DSS colitis, where it dose-dependently inhibited colon GCPII, attenuated both gross disease activity index and blinded colon histopathology scores, and had improved efficacy relative to both sulfasalazine and tofacitinib when compared head-to-head. Mechanistically, we determined that IBD3540 attenuated pathogenic monocytic inflammation in the colon, as measured by flow cytometry, and also decreased colon pro-inflammatory cytokine content. We confirmed efficacy of IBD3540 in spontaneously occurring, chronic, IL10 -/- colitis, where treatment initiated 4 weeks after the onset of colon inflammation improved multiple disease endpoints. Further, in preclinical safety screens, inclusive of CYP inhibition/induction assays, Eurofins SafetyScreen44 TM, and AMES/hERG mutagenicity testing, no concerns were identified. Conclusion: IBD3540 is a novel, gut-restricted, GCPII inhibitor with potent oral anti-colitis efficacy in both acute (DSS) and chronic (IL10 -/- ) mouse colitis models and a promising preclinical safety profile. Further development of this mechanistically unique candidate IBD drug is warranted.